Negotiating Gender and Language Barriers: Dual Roles of Vietnamese Married Immigrant Women in Taiwan - Quoc Tuan Huynh (Journal of Research in Social Sciences and Language)
This article examines the evolving roles of Vietnamese married immigrant women in Taiwan, focusing on their experiences as primary breadwinners within the family. Drawing on Zimmerman’s concept of "doing gender," it explores how these women handle traditional gendered expectations while fulfilling their roles as earners and caregivers. Through in-depth interviews with 13 Vietnamese women, the study highlights how they perceive self-sacrifice and suffering as integral to their sense of dignity. The article demonstrates that while caregiving remains central to their understanding of womanhood, these women view the breadwinner role as both a responsibility and a means to challenge the stigma of being a “bad mother.” The article further reveals how language barriers shape their life and influence power dynamics within the family. The study contributes to the broader discourse on gender, migration, and caregiving; offering insights into the complex intersection of cultural norms, familial obligations, and women’s agency in transnational contexts. Future research could examine how transnational caregiving and breadwinning roles reshape gender norms and family dynamics over time.